An identification protocol for ESBL‐producing Gram‐negative bacteria bloodstream infections using a MinION nanopore sequencer. Issue 8 (August 2019) - Sakai, Jun; Tarumoto, Norihito; Kodana, Masahiro; Ashikawa, Sae; Imai, Kazuo; Kawamura, Toru; Ikebuchi, Kenji; Murakami, Takashi; Mitsutake, Kotaro; Maeda, Takuya; Maesaki, Shigefumi
Abstract : Purpose. : The new third‐generation sequencing platform MinION is an attractive maintenance‐free and disposable portable tool that can perform long‐read and real‐time sequencing. In this study, we validated this technology for the identification of pathogens from positive blood culture (BC) bottles. Methodology. : A total of 38 positive BC bottles were collected from patients with bloodstream infections, and 18 isolates of Gram‐negative (GN) bacteria and 20 isolates of Gram‐positive (GP) bacteria were identified from these using 16S rRNA sequencing and then used in this study. DNA was extracted from each aliquot using an extraction protocol that combined glass bead beating and chemical lysis. Up to 200 ng of each purified DNA sample was processed for library preparation and whole‐genome sequencing was performed on up to 12 samples through a single MinION flow cell. Results. : All GN bacteria identifications made by MinION sequencing for 30 min using the What's In My Pot? (WIMP) workflow via EPI2ME on the basis of the most frequent classified reads were consistent with those made by 16S rRNA sequencing. On the other hand, for GP bacteria specimens, the identification results for 16S rRNA sequencing and MinION were only in agreement in 12 out of 20 (60.0 %) cases. ARMA analysis was able to detect extended‐spectrum β ‐lactamase (ESBL)‐associated genes among various antimicrobial resistance‐related genes. Conclusion. : We demonstrated the potential of the MinION sequencer for the identification of GN bacteria from positive BC bottles and the confirmation of an ESBL phenotype. This innovative sequence technology and its application could lead to a breakthrough in the diagnosis of infectious diseases.